THE DEVELOPMENT OF INTERACTIVE FLASH MULTIMEDIA BASED ON PROBLEM BASED LEARNING OF SD SCIENCE LESSONS - Hidayah, Nurul; Sulistyorini, Sri (Elementary School Teacher, 2020)
The purpose of this study was to determine the characteristics and viability of flash interactive multimedia based on problem-based learning on single and mixed substances topic of natural sciences subject. The type of this study was Research and Development (R&D). The development model used is the Borg & Gall model adapted by Sugiyono with several stages adapted to the needs of the researcher. The data collection techniques used observation, interviews, documentation, and questionnaires. The results showed that (1) flash interactive multimedia matched with the characteristics of the problem-based learning model; (2) flash interactive multimedia was suitable to be used as a learning media, based on the result of the media expert's validation with a percentage of 83% with the very viable category and the result of the content expert ' s validation with a percentage of 86% with the very viable category. The conclusion of this research was the developed flash interactive multimedia based on problem-based learning was appropriate to be used as a learning media on single and mixed substances topic of natural sciences in the fourth grade at Kalibanteng Kidul 02 Elementary School, Semarang City.